The Challenge of Madrasah in Facing the VUCA Era (The Readiness of Islamic Madrasah Education System in Facing Digital Era) - Supa'at, Supa'at; Munir AP, Muh Misbahul; Rizqi, Fitria Noor Lailatur (International Journal of Social Learning (IJSL), 2025)
In the rising of VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era characterized by rapid change and uncertainty, the education system faces major challenges. In Indonesia, educational institutions, including Islamic school, must adapt policies and strategies to remain relevant and effective. This research focuses on the Islamic senior high schools (Madrasah Aliyah /MA) in facing the digital era by exploring the readiness of the madrasah education system in overcoming the VUCA era challenges. This research uses qualitative approach with descriptive method and purposive sampling technique. The research has been conducted at MAN 1 Kudus, MAN 2 Kudus, and MA NU Banat. Subject of this research were the headmasters, stakeholders, teachers, and students. Data collection techniques include interviews, observation, and documentation. The data were then analyzed using triangulation. The result revealed that those schools were ready to face the digital challenge in terms of human resources, material, method and facilities. This research is expected to provide insight into curriculum adaptation, use of technology, and strengthening student character as an effort to achieve the vision of Indonesian education.